La saveur du cœur et l’amertume du corps - Karen Shiratori; Daniel Cangussu (Revue d'ethnoécologie)
In light of the recent ethnographic production on the indigenous Arawá peoples and the research in historical ecology dedicated to the lands of the Juruá-Purus interfluve, this article proposes a reflection on plant poisons, hunting and fishing, based on the sociality, shamanism and body-making practices of the indigenous peoples of this region. We start from the self-poisoning of the Suruwaha to consider it as a starting point for the analysis of the language of the physiology of Arawá affections that expresses the ambivalence or categorical instability of certain plants. Our hypothesis is that the use and importance of plants in the Arawá context is inseparable from their anti-alimentary value, i.e., their food and practical aspects do not obliterate their shamanic potential as poisons. In the first part of the text, we present a reflection on Casimirella ampla, a tuberous plant, which offers a productive perspective on the use of cassava in this region and will serve as an analytical model to test the hypothesis on the practical and categorical ambivalence of certain plants. In the second part, we develop our argument by highlighting the anti-alimentary potential of these plants, in favor of an alternative conceptual image of Arawá sociability in which poisons are featured as body transforming substances.